Edge effects on tree architecture exacerbate biomass loss of fragmented Amazonian forests - Nunes Matheus Henrique; Vaz Marcel Carita; Camargo Jose Luis Campana; Laurance William F.; de Andrade Ana; Vicentini Alberto; Laurance Susan; Raumonen Pasi; Jackson Toby; Zuquim Gabriela; Wu Jin; Penuelas Josep; et al. (Springer Nature, 2025)
Habitat fragmentation could potentially affect tree architecture and allometry. Here, we use ground surveys of terrestrial LiDAR in Central Amazonia to explore the influence of forest edge effects on tree architecture and allometry, as well as forest biomass, 40 years after fragmentation. We find that young trees colonising the forest fragments have thicker branches and architectural traits that optimise for light capture, which result in 50% more woody volume than their counterparts of similar stem size and height in the forest interior. However, we observe a disproportionately lower height in some large trees, leading to a 30% decline in their woody volume. Despite the substantial wood production of colonising trees, the lower height of some large trees has resulted in a net loss of 6.0 Mg ha−1 of aboveground biomass – representing 2.3% of the aboveground biomass of edge forests. Our findings indicate a strong influence of edge effects on tree architecture and allometry, and uncover an overlooked factor that likely exacerbates carbon losses in fragmented forests.